Embodied gestures - Tomás, Enrique; Gorbach, Thomas; Tellioglu, Hilda; Kaltenbrunner, Martin (TU Wien Academic Press, 2022)
This is a book about musical gestures: multiple ways to design instruments, compose musical performances, analyze sound objects and represent sonic ideas through the central notion of 'gesture'. The writers share knowledge on major research projects, musical compositions and methodological tools developed among different disciplines, such as sound art, embodied music cognition, human-computer interaction, performative studies and artificial intelligence. They visualize how similar and compatible are the notions of embodied music cognition and the artistic discourses proposed by musicians working with 'gesture' as their compositional material. The authors and editors hope to contribute to the ongoing discussion around creative technologies and music, expressive musical interface design, the debate around the use of AI technology in music practice, as well as presenting a new way of thinking about musical instruments, composing and performing with them.